FGD1 Variant Associated With Aarskog–Scott Syndrome - Zhu, Yilin; Chen, Qingqing; Lin, Haiyan; Lu, Huifei; Qu, Yangbin; Yan, Qingfeng; Wang, Chunlin (Frontiers in Pediatrics, 2022)
Background Aarskog–Scott syndrome, a rare X-linked genetic disorder, is identified by combined clinical manifestations of short stature, facial, skeletal, and genital anomalies. Annually, two or three new cases are diagnosed with Aarskog–Scott syndrome, which is associated with FGD1 variants. However, there is no specific treatment for Aarskog–Scott syndrome due to its unclear mechanism. Methods Clinical data were collected when the patient first visited the hospital. Trio whole-exome sequencing and Sanger sequencing were performed for the genetic cause of disease. To evaluate the pathogenicity of the variants in vitro, stable cell lines were constructed using lentivirus infection in 143B cell. Furthermore, Western blot was used to verify the expression of signaling pathway-related proteins, and the transcription levels of osteogenic-related genes were verified by luciferase reporter gene assay. Results A 7-year-old boy was manifested with facial abnormalities, intellectual disability, and short stature (−3.98 SDS) while the growth hormone level of stimulation test was normal. Trio whole-exome sequencing and Sanger sequencing identified a variant (c.1270A>G, p.Asn424Asp) in FGD1 gene. The Asn424 residue was highly conserved and the hydrogen bond in the FGD1 variant protein has changed, which led to decrease in the interaction with CDC42 protein. In vitro study showed that the Asn424Asp variant significantly decreased the transcription levels of OCN, COL1A1, and ALP activity, and it activated the phosphorylation of JNK1. Conclusion Molecular biological mechanisms between abnormal expression of FGD1and Aarskog–Scott syndrome remain poorly understood. In our study, c.1270A>G variant of FGD1 resulted in Aarskog–Scott syndrome, and the analysis of pathogenicity supports the deleterious effect of the variant. Furthermore, we demonstrated the weakened affinity of the mutant FGD1 and CDC42. Decreased expression of osteogenic-related gene and abnormal activation of JNK1 were also shown in this work.